Design and implementation of an automated transformer monitoring system - Purno, Mumtahina Tasnim; Sayeed, Shahtaz Zahra; Ahmed, Faiza; Das, Sarthak; Rahaman, Minhajur (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.